2018
DOI: 10.1097/sla.0000000000002186
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthetic, Host-defense Peptide Protects Against Organ Injury/Dysfunction in a Rat Model of Severe Hemorrhagic Shock

Abstract: Trauma-associated HS results in release of LL-37. The synthetic host-defense/antimicrobial peptide Pep19-4LF attenuates the organ injury/dysfunction associated with HS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…Protein isolation and Western blot analysis. Semiquantitative Western blot analysis of caspase-3, caspase-9, Bax, and Bcl-2 was performed in murine heart tissue as previously before (48,49). For protein isolation, the tissue was homogenized in homogenization buffer (20 mM HEPES, pH 7.9, 1 mM MgCl 2 , 0.5 mM EDTA, 1% Nonidet P-40, 1 mM EGTA, 1 mM DTT, 0.5 mM PMSF, 1 μL/mL PIC) and centrifuged by 18,800 g for 40 minutes at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Protein isolation and Western blot analysis. Semiquantitative Western blot analysis of caspase-3, caspase-9, Bax, and Bcl-2 was performed in murine heart tissue as previously before (48,49). For protein isolation, the tissue was homogenized in homogenization buffer (20 mM HEPES, pH 7.9, 1 mM MgCl 2 , 0.5 mM EDTA, 1% Nonidet P-40, 1 mM EGTA, 1 mM DTT, 0.5 mM PMSF, 1 μL/mL PIC) and centrifuged by 18,800 g for 40 minutes at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…ELISA for ANXA1 Concentrations of ANXA1 in human plasma, mouse serum or protein lysates from heart and kidney were measured by ELISA as previously reported [21][22][23] /Tyr 204 on extracellular signal-regulated kinase (ERK1/2)/p-ERK1/2 (New England Biolabs) was measured by semi-quantitative western blot analyses in mouse heart and kidney tissue as described previously [20,25] (see ESM Methods for further details).…”
Section: Methodsmentioning
confidence: 99%
“…Activated Akt controls inflammatory and pro-survival responses [44]. Most notably, activation of the Akt survival pathway reduces organ injury in many conditions associated with inflammation including sepsis-induced organ dysfunction [20,45], haemorrhagic shock-induced organ dysfunction [25,46], myocardial infarction [47] and diabetes [48]. Specifically, in cardiac and renal ischaemia/reperfusion injury treatment with the Ac2-16 peptide tissue necrosis was reduced by activation of Akt [49,50].…”
mentioning
confidence: 99%
“…Currently, there is no specific treatment for postoperative organ failure/dysfunction after TAAA repair, which is associated with high morbidity and mortality. We recently reported that a synthetic host-defense peptide that targets heparanase and heparan sulfate attenuates the organ injury/dysfunction associated with hemorrhagic shock (39, 40). Thus, we postulate that synthetic host-defense peptides may be promising therapeutics against postoperative organ failure/dysfunction after TAAA repair.…”
Section: Discussionmentioning
confidence: 99%